2018
DOI: 10.1039/c8cp00818c
|View full text |Cite
|
Sign up to set email alerts
|

CO2 adsorption on gas-phase Cu4−xPtx (x = 0–4) clusters: a DFT study

Abstract: Transition and noble metal clusters have proven to be critical novel materials, potentially offering major advantages over conventional catalysts in a range of value-added catalytic processess such as carbon dioxide transformation to methanol. In this work, a systematic computational study of CO2 adsorption on gas-phase Cu4-xPtx (x = 0-4) clusters is performed. An exhaustive potential energy surface exploration is initially performed using our recent density functional theory basin-hopping global optimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 63 publications
3
29
0
Order By: Relevance
“…80 CO 2 adsorption on gas-phase Cu 4Àx Pt x (x = 0-4) was investigated using DFT calculations. High adsorption energies (from À78 to À158 kJ mol À1 ) and CO 2 adsorption in a bent mode were found, 81 and could be explained by charge transfer towards the cluster's LUMO. 82 Based on the reversible structural transformation, the optimal strength of the interaction between the cluster and the adsorbent, and the low CO 2 dissociation barrier, Cu 3 Pt is a promising catalyst.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…80 CO 2 adsorption on gas-phase Cu 4Àx Pt x (x = 0-4) was investigated using DFT calculations. High adsorption energies (from À78 to À158 kJ mol À1 ) and CO 2 adsorption in a bent mode were found, 81 and could be explained by charge transfer towards the cluster's LUMO. 82 Based on the reversible structural transformation, the optimal strength of the interaction between the cluster and the adsorbent, and the low CO 2 dissociation barrier, Cu 3 Pt is a promising catalyst.…”
Section: Introductionmentioning
confidence: 95%
“…82 Based on the reversible structural transformation, the optimal strength of the interaction between the cluster and the adsorbent, and the low CO 2 dissociation barrier, Cu 3 Pt is a promising catalyst. 81 It was shown, that Ni-or Pd-doped Cu 4 clusters exhibit higher adsorption energy and promote the CO 2 activation, because the dopant enhances the charge transfer between the cluster and the adsorbent. 83 Although none of these clusters decrease the CO 2 dissociation barrier.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption technology is costly and requires a high amount of energy (3). Meanwhile, membrane separation technologies hold promise of great energy savings, high selectivity, and therefore lower costs when compared to other conventional methods (7)(8)(9)(10). This technology combines the membrane separation capability with adsorption activities of adsorbents for gas/liquid molecules separation and thus, it is considered as a most efficient technique compared to solo adsorption (7).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, membrane separation technologies hold promise of great energy savings, high selectivity, and therefore lower costs when compared to other conventional methods (7)(8)(9)(10). This technology combines the membrane separation capability with adsorption activities of adsorbents for gas/liquid molecules separation and thus, it is considered as a most efficient technique compared to solo adsorption (7). Further benefits of membrane systems are smaller footprints and easy to scale-up making this technology an appropriate candidate for industrial applications (11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…12,[202][203][204] For 4-atom clusters based on Cu or Pt, it was reported that bimetallic systems affect the OCO angle of adsorbed CO 2 differently than the unary nanoclusters and extended surfaces. [205][206][207] For Pt nanoparticles, alloying with Co atoms to form Pt 3 Co octapods can promote CO 2 activation and improve the catalytic activity in comparison to unary Pt systems. 208 Besides the type of TM, the proportion of each component of the nanoalloy is critical to design better catalysts; for example, the composition of PdAg alloys can be tuned to weaken the binding of CO with respect to other intermediates during the electroreduction of CO 2 .…”
Section: Introduction and State Of The Artmentioning
confidence: 99%